The association of padded headgear with concussion and injury risk in junior Australian football: A prospective cohort study - Makovec Knight, J.; Mitra, B.; McIntosh, A.; Howard, T. S.; Clifton, P.; Makdissi, M.; Rosenfeld, J. V.; Harcourt, P.; Willmott, C. (Journal of Science and Medicine in Sport, 2022)
Objectives: To assess whether padded headgear was associated with incidence of suspected sports-related concussion, non-sports-related concussion head injury, and injuries to other body regions in junior Australian football. Design: Prospective cohort injury surveillance. Methods: There were 400 junior players (42.5% female) enrolled across two seasons. Suspected sports-related concussion was defined by detection of observable signs on the field and medical assessment or missed match(es) due to suspected sports-related concussion. Non-sports-related concussion head injury and injuries to other body regions were defined as those that received medical assessment or resulted in a missed match. Results: There were 20 teams monitored over 258 matches. 204 players (2484 player hours) wore mandated headgear throughout the season and 196 (2246 player hours) did not. The incidence rate of suspected sports-related concussion was 3.17 (95% confidence interval: 3.04-3.30) per 1000 player-hours and no differences were observed between males and females (risk ratio 1.11; 95% confidence interval: 0.40-3.06). Headgear use was not associated with suspected sports-related concussion (risk ratio 1.09; 95% confidence interval: 0.41?2.97), non-sports-related concussion head injury (risk ratio 0.27; 95% confidence interval: 0.06?1.31), or injuries to other body regions (risk ratio 1.41; 95% confidence interval: 0.79?2.53). Conclusions: Headgear use was not associated with reduced risk of suspected sports-related concussion, non-sports-related concussion head injury or injuries to other body regions. There was no difference in the rate of suspected sports-related concussion in female compared to male players, however, rates of non-sports-related concussion head injury and injuries to other body regions were higher in male players. Objectives: To assess whether padded headgear was associated with incidence of suspected sports-related concussion, non-sports-related concussion head injury, and injuries to other body regions in junior Australian football.